Case Report: Uniportal robot-assisted thoracoscopic double-sleeve lobectomy after neoadjuvant immunotherapy - Fang, Ziyao; Li, Chang; Bosinceanu, Mugurel L.; Ding, Cheng; Zhao, Jun; Gonzalez-Rivas, Diego (Frontiers in Surgery, 2024)
Minimally invasive thoracic surgery, including video-assisted thoracoscopic surgery and robot-assisted thoracoscopic surgery, has been proven to have an advantage over open thoracotomy with less pain, fewer postoperative complications, faster discharge, and better tolerance among elderly patients. We introduce a uniportal robot-assisted thoracoscopic double-sleeve lobectomy performed on a patient following neoadjuvant immunotherapy. Specialized instruments like customized trocars with a reduced diameter, bulldog clamps, and double-needle sutures were utilized to facilitate the maneuverability through the single incision. This technique integrates the merits of multiport robot-assisted thoracic surgery with uniportal video-assisted thoracoscopic surgery.